ACTIVE PLAY INTERVENTIONS ON MOTOR SKILLS OF PRESCHOOLERS: A SYSTEMATIC REVIEW - Santiago, Fátima Larissa (2022)
Active play can contribute to the reduction of sedentary time and generate potential benefits for the performance of fundamental motor skills in children. Thus, the aim of this systematic review was to provide a synthesis of evidence on the contributions of active play to fundamental motor skills in children aged 2 to 5 years typically developed, as well as to verify the differences between the intervention protocols used in the studies. The studies were identified by searching the PubMed, Web of Science and Lilacs databases. Clinical trials available in English, conducted in typically developing children, were included, and studies with the theme of electronic games were excluded. Two independent researchers examined the studies and conducted data extraction. Eight articles were included in the systematic review; three identified that children who experienced interventions with free active play had better performance in handling and balance skills. Four studies identified that children who practiced guided active play had better performance in locomotion, manipulation and balance skills, one study found no significant difference. We concluded that the practice of active play, especially guided active play, positively contributes to the fundamental motor skills of children aged 3 to 5 years typically developed.